A literature review of the research on students’ evaluation of teaching in higher education - Zhao, Luying; Xu, Pei; Chen, Yusi; Yan, Shuangsheng (Frontiers in Psychology, 2022)
Abstract: Students’ evaluation of teaching is a teaching quality evaluation method and teacher performance evaluation tool commonly used in Chinese and foreign universities, and it is also a controversial hot issue in the field of teaching evaluation. At present, the research results of students' evaluation of teaching in higher education are relatively rich, mainly focusing on reliability, validity and its influencing factors, construction of index system, problems in practical application and improvement strategies. The purpose of this paper is to study the relevant research results of the current Chinese and foreign academic circles, in order to provide useful inspiration for the construction of the index system and practical application of the ideological and political theory course evaluation and teaching of Chinese college students . Key words: students’ evaluation of teaching; review; higher education; indicator systems ; comments.